analisis respon siswa Analisis Respon Siswa dalam Menyelesaikan Masalah Matematika Berdasarkan taksonomi SOLO Ditinjau dari Gender - Fatikhah, Wulan; Sukoriyanto; Rahayuningsih, Sri (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to determine the level of student responses based on SOLO Taxonomy in solving math problems in terms of gender perspective at SDN Sutojayan 2 Blitar Regency. The method used in this research is a qualitative method with a phenomenological approach to obtain information from participants about the responses given. The subjects in this study were 6 female students and 6 male students in grade V, grade V math teacher, and principal. Data collection techniques used in this study were observation, tests, interviews and documentation. This study used tests to categorize students in five levels of SOLO taxonomy namely prestructural, unistructural, multistructural, relational, and extended abstract levels. The result of this study is that female students have a higher level of understanding, accuracy, and perseverance than male students so that it affects the responses given. Thus the results of the study can be concluded that female students are at a higher level than male students, namely at the relational level and men are at the multistructural level.